Biodiesel from transesterification at low temperature by AlCl3 catalysis in ethanol and carbon dioxide as cosolvent: Process, mechanism and application. (15th February 2016) - Guan, Qingqing; Shang, Hua; Liu, Jing; Gu, Junjie; Li, Bin; Miao, Rongrong; Chen, Qiuling; Ning, Ping
Graphical abstract: Highlights: A rapid, efficient method of transesterification leading to production of biodiesel is developed using AlCl3 and CO2 . The utility of the process has been demonstrated by the production of BD from waste cooking oil (WCO). The method holds the promise of an integrated process for the production of BD from algae. Abstract: Finding a more efficient method for the transesterification of triglycerides to biodiesel fuel (BD) is important in today's world. In this study, transesterification of trilaurin was carried out in a solution containing 4 wt% of the Lewis acid AlCl3 dissolved in a cosolvent of ethanol and 5 MPa CO2 . A conversion rate of over 90% was achieved within 1 h at the low temperature of 180 °C. The process indicates a co-catalytic effect of the Lewis acid and CO2 . We postulate several key steps for the mechanism. First, the CO2 –ethanol mixture enhances the hydrogen bonding, increasing the concentration of C2 H5 O . Second AlCl3 attacks the oxygen of COC to weaken the bonds to form carbonyl carbon OR1, which is then easily attacked by C2 H5 O to give the transesterified product (C2 H4 COOR1). Third, AlCl3 is finally replaced by H to form glycerin (GL) and intermediates, such as unmethyl esterified compounds (uME). AlCl3 was used as a flocculant and catalyst for converting waste cooking oil (WCO) to BD. The process achieved 97% free fatty acid (FFA) conversion at 120 °C in 90 min, making it one of the most efficient systems available for WCO recovery. AlCl3 was also successfully applied to microalgae, signaling the potential for a process that combines harvesting, lipid extraction, and transterification, leading to fully integrated, microalgae-based BD production.